Complications and outcomes of tubeless versus nephrostomy tube in percutaneous nephrolithotomy: A systematic review and meta-analysis of randomized clinical trials - Gauhar, Vineet; Traxer, Olivier; Rojo, Esther Garcia; Scarcella, Simone; Pavia, Maria Pia; Chan, Vinson Wai-Shun; Pretore, Eugenio; Wroclawski, Marcelo Langer; Corrales, Mariela; Tiong, Ho Yee; Lim, Ee Jean; Teoh, Jeremy Yuen-Chun; et al. (Springer, 2022)
We aimed to perform a systematic review of randomized trials to summarize the evidence on the safety and stone-free rate after Tubeless percutaneous nephrolithotomy (PCNL) (ureteral stent/catheter, no nephrostomy) compared to Standard PCNL (nephrostomy, with/without ureteral stent/catheter) to evaluate if the tubeless approach is better. The inverse variance of the mean difference with a random effect, 95% Confidence Interval (CI), and p values was used for continuous variables. Categorical variables were assessed using Cochran-Mantel-Haenszel method with the random effect model, and reported as Risk Ratio (RR), 95% CI, and p values. Statistical significance was set at p < 0.05 and a 95% CI. 26 studies were included. Mean operative time was significantly shorter in the Tubeless group (MD-5.18 min, 95% CI - 6.56, - 3.80, p < 0.00001). Mean postoperative length of stay was also significantly shorter in the Tubeless group (MD-1.10 day, 95% CI - 1.48, - 0.71, p < 0.00001). Incidence of blood transfusion, angioembolization for bleeding control, pain score at the first postoperative day, the number of patients requiring postoperative pain medication, fever, urinary infections, sepsis, perirenal fluid collection, pleural breach, hospital readmission, and SFR did not differ between the two groups. Incidence of postoperative urinary fistula was significantly lower in the Tubeless group (RR 0.18, 95% CI 0.07, 0.47, p = 0.0005). This systematic review shows that tubeless PCNL can be safely performed and the standout benefits are shorter operative time and hospital stay, and a lower rate of postoperative urinary fistula.
Keywords: Ambulatory Surgical Procedures; Kidney Stone; Percutaneous Nephrolithotomy; Percutaneous Nephrostomy